Sexting, grooming, stalking and sexual harassment among high school adolescents in Mexico - Fuensanta López Rosales; José Luis Jasso Medrano (Revista de Psicología y Ciencias del Comportamiento de la Unidad Académica de Ciencias Jurídicas y Sociales)
The purpose of the study was to compare sexting, grooming, stalking, and sexual harassment beha-viors in high school students in the state of Vera-cruz based on sociodemographic variables. The sample included 204 students (14-19 years old) who answered a sociodemographic form, the AMAI 2022 test, the sexual harassment question-naire for medical students (CASEM, Silva, 2013), the sexting questionnaire (Gámez-Guadix, et al., 2015) and the adult solicitation and interaction questionnaire (Gámez-Guadix, et al., 2017). A total of 77.9% indicated some type of sexual harassment and stalking, 39.2% sexting and 52.5% grooming. Sexual harassment and bullying were higher in females, sexting was higher in males, and groo-ming was similar in both sexes. There were no dif-ferences based on socioeconomic level, while a sexual orientation other than heterosexual or using social networks for more than 6 hours increases the presence of the variables.